Issues of Human Resource Management (IntechOpen, 2023)
The book "Issues of Human Resource Management", written by well-known authors, is a result of a teamwork of specialists who have been dealing with the issue of managing human resources in different contexts. The authors from Germany, Spain, Turkey, Slovakia and Romania have submitted results of their current research and have presented important findings that are becoming a starting point for making managers decision so that their businesses can be competitive. You have put your hands on a selection of the best scientific contributions that have been reviewed and now are offering a space for an active debate on partial issues of the given topic. The authors in their work examined also the factors of psychology applied in HRM, the organisation of companies and its impact on human resource management, workers motivation and incentives and investment into human resources development; they searched the field of human resource management in family businesses, the quality of relationship in a workplace and specifics of human resource management in non-governmental organisation.